The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.17718/tojde.415827
|View full text |Cite
|
Sign up to set email alerts
|

A Content Analysis of Dissertations in the Field of Educational Technology: The Case of Turkey

Abstract: The present study aimed at conducting content analysis on dissertations carried out so far in the field of Educational Technology in Turkey. A total of 137 dissertations were examined to determine the key words, academic discipline, research areas, theoretical frameworks, research designs and models, statistical analyses, data collection tools, participants, instructional design models, variables/research focus and related institutions. When the research results were examined, it was found in relation to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 9 publications
5
3
0
3
Order By: Relevance
“…Qualitative research across the theses often consisted of single or multiple case studies as well as experimental and phenomenological research, while correlational studies, quasi-experimental, or descriptive research were mainly utilized in master's and doctoral theses adopting a quantitative approach. These findings are in accordance with the latest research syntheses (e.g., Durak et al, 2018;Şişman et al, 2019), but not in other studies, in which quantitative research design was found to be the most commonly used methodology in both educational technology and ELT research (e.g., Göktaş et al, 2012;İnal et al, 2016;Küçük et al, 2013;Solak, 2014;Yağız et al, 2016). This finding is perhaps not surprising given the present synthesis covers the period of 2016 and 2020, and there is an upward trend in tendency to use mixed-methods design in the recent years as indicated in the fields of educational technology (e.g., Durak et al, 2017) and ELT (Şişman et al, 2019).…”
Section: Findings Related To Content Features Of Thesessupporting
confidence: 88%
See 1 more Smart Citation
“…Qualitative research across the theses often consisted of single or multiple case studies as well as experimental and phenomenological research, while correlational studies, quasi-experimental, or descriptive research were mainly utilized in master's and doctoral theses adopting a quantitative approach. These findings are in accordance with the latest research syntheses (e.g., Durak et al, 2018;Şişman et al, 2019), but not in other studies, in which quantitative research design was found to be the most commonly used methodology in both educational technology and ELT research (e.g., Göktaş et al, 2012;İnal et al, 2016;Küçük et al, 2013;Solak, 2014;Yağız et al, 2016). This finding is perhaps not surprising given the present synthesis covers the period of 2016 and 2020, and there is an upward trend in tendency to use mixed-methods design in the recent years as indicated in the fields of educational technology (e.g., Durak et al, 2017) and ELT (Şişman et al, 2019).…”
Section: Findings Related To Content Features Of Thesessupporting
confidence: 88%
“…The data were collected through participant work (6.35%, f=24) as well, which featured documents such as online peer feedback comments, participants' lesson plans, assignments, learner essays, blog posts, and discussion forum posts. These findings are in tune with the literature, in which survey/questionnaire, interviews, and achievement tests were commonly reported among the preferred data collection tools (e.g., Durak et al, 2018;Göktaş et al, 2012;Solak, 2014) As displayed in Table 8, the gathered data were analyzed by means of quantitative (i.e., descriptive analysis and inferential analysis) and qualitative analyses. Quantitative analysis was the most preferred data analysis method across both master's theses (59.84%, f=149) and doctoral theses (62.5%, f=30).…”
Section: Findings Related To Content Features Of Thesessupporting
confidence: 77%
“…Farklı alanlarda da benzer araştırma eğilimlerinin incelendiği çalışmalar yer almaktadır. Örneğin teknoloji alanında yapılan, bu araştırma sonuçları ile benzer olarak araştırmalarda yöntem olarak daha çok nicel, örneklem olarak daha çok lisans öğrenciler, veri analiz yöntemi olarak en fazla betimsel analizler yapıldığı sonucuna ulaşan çalışmalar yer almaktadır (Durak, Cankaya, Yunkul ve Misirli, 2018;Göktaş vd., 2012;Kılıç Çakmak vd., 2015;Küçük vd., 2013). Araştırma eğilimlerinin incelendiği çalışmalar o alanda çalışılmayan, eksik kalan konuların, yöntemlerin, örneklem gruplarının ortaya çıkarılması açısından önemlidir.…”
Section: Sonuç Tartişma Ve öNeri̇lerunclassified
“…Analiz yöntemleri ele alındığında gerek tez inceleme çalışmalarında (Durak, Cankaya, Yunkul, & Mısırlı, 2018;Tosuntaş, Emirtekin, & Süral, 2019) gerekse sempozyum analizinde ortaya çıkan önemli bir nokta anova, ancova gibi istatiksel analizlerle, parametrik olmayan analizlerin daha az tercih edildiğidir. Ayrıca, her iki tez analiz çalışmasıyla karşılaştırıldığında konferanslarda alan yazın derleme çalışmalarına temel oluşturan içerik analizinin daha yüksek oranda olduğu ifade edilebilir.…”
Section: Araştırmanın öNemi Ve Amacıunclassified
“…Tarama desenini deneysel çalışmalar (%27.0), ilişkisel çalışmalar (%5.1) ve nedensel karşılaştırma çalışmalarının (%2.2) takip ettiği raporlanmıştır. Araştırmacılar nitel çalışmalar ise örnek olay (%17.5) ve eylem araştırması (%7.3) olarak raporlamışlardır(Durak, Cankaya, Yunkul, & Mısırlı, 2018). Tez çalışmalarının araştırma desenleri, tarama ve deneysel çalışmalar açısından büyük ölçüde birbiriyle örtüşmektedir.…”
unclassified